Kombinasi Imajinasi Terpimpin dan Nafas Dalam terhadap Penurunan Kecemasan Pasien dengan Premature Ventricular Contraction (PVC) - Kurniawati, Ninuk Dian; Sila, Nissa Aruming; Ariningpraja, Rustiana Tasya; Hariyati, Leli Ika; Suciari, Ana (Journal of Telenursing (JOTING), 2024)
This study aims to explore interventions to prevent anxiety in Premature ventricular complex (PVC) patients in the ICCU treatment room. This research method uses a case study approach on three patients with PVC with almost the exact etiology and experiencing anxiety since the start of treatment and a combination of interventions carried out for three consecutive days. The results show that there are differences in anxiety parameters before and after intervention in each patient. Anxiety parameters were assessed from the first day to the third day, respectively, before the intervention and after the intervention. Conclusion: The combination of guided imagery intervention and deep breathing relaxation can help reduce anxiety in patients with PVC. Keywords: Guided imagination, Anxiety, Deep Breathing, Premature Ventricular Complex